Histologic Antibody-mediated Kidney Allograft Rejection in the Absence of Donor-specific HLA Antibodies. Issue 11 (November 2021) - Filippone, Edward J.; Farber, John L.
Abstract : Histologic antibody-mediated rejection (hAMR) is defined as a kidney allograft biopsy satisfying the first 2 Banff criteria for diagnosing AMR: tissue injury and evidence of current/recent antibody interaction with the endothelium. In approximately one-half of such cases, circulating human leukocyte antigen (HLA) donor-specific antibodies (DSA) are not detectable by current methodology at the time of biopsy. Some studies indicated a better prognosis for HLA-DSA-negative cases of hAMR compared to those with detectable HLA-DSA, whereas others found equally poor survival compared to hAMR-negative cases. We reviewed the literature regarding the pathophysiology of HLA-DSA-negative hAMR. We find 3 nonmutually exclusive possibilities: (1) HLA-DSA are involved, but just not detected; (2) non-HLA-DSA (allo or autoantibodies) are pathogenically involved; and/or (3) antibody-independent NK cell activation is mediating the process through "missing-self" or other activating mechanisms. These possibilities are discussed in detail. Recommendations regarding the approach to such patients are made. Clearly, more research is necessary regarding the measurement of non-HLA antibodies, recipient/donor NK cell genotyping, and the use of antibody reduction therapy or other immunosuppression in any subset of patients with HLA-DSA-negative hAMR.